Focus on Indian Homoeopathic Educational Sector (Homoeopathy for All, 2025)
Homoeopathy is a widely practiced  system of alternative medicine in  India, founded on the principle of  "like cures like." Its journey in the  country began in the early 19th  century, with Bengal playing a  crucial role in its initial development  in India. The system gained traction  in both civil and military sectors,  thanks in part to Dr Mahendra Lal  Sarkar, recognized as the first Indian  homoeopath. A landmark in this  progress was the establishment of the  “Calcutta Homoeopathic Medical  College & Hospital” in 1881—the  oldest homoeopathic institution in  Asia. This college continues to offer  BHMS (Bachelor of Homoeopathic  Medicine and Surgery) and MD  programs, is affiliated with the West  Bengal University of Health Sciences  (WBUHS), and is recognized  by the National Commission for  Homoeopathy (NCH) under the  Ministry of AYUSH.
Keywords: widely; practiced; alternative; medicine